Effect of Neuromuscular Blockade Reversal on Postoperative Gastrointestinal Motility after Laparoscopic Cholecystectomy: Neostigmine / Atropine versus Sugammadex - Bayram, Murat; Yakan, Savas; Barut, Fulya Yilmaz; Bas, Koray (Journal of the College of Physicians and Surgeons--Pakistan, 2024)
To compare sugammadex with neostigmine / atropine combination for reversal of neuromuscular blocker agents in terms of postoperative gastrointestinal motility in patients who underwent laparoscopic cholecystectomy. Experimental study. Place and Duration of the Study: University of Health Sciences, Izmir Bozyaka Training and Research Hospital, Izmir, Turkiye, between December 2020 and June 2021. Seventy-two patients undergoing laparoscopic cholecystectomy were included. At the end of the surgery, patients were antagonised for neuromuscular blockers either by atropine / neostigmine or sugammadex by an anaesthesiologist who was not involved in the study. Total anaesthesia time, pneumoperitoneum time, surgery time, number of postoperative opioid dose requirements and total opioid dose administered, number of medication requirements for postoperative nausea and vomiting, postoperative hospital stay, and first gas and stool output time of all the cases were evaluated by the researcher who was unaware of the medicines used for antagonisation. There were no statistically significant differences between the two groups in terms of their effects on postoperative gastrointestinal motility (first gas and stool output time), duration of anaesthesia, duration of surgery, duration of pneumoperitoneum, the number of postoperative opioid dose requirements, the number of drug requirements for postoperative nausea / vomiting, and the postoperative hospitalisation duration of the cases. Effects of reversal agents on postoperative gastrointestinal motility are still debated. Studies on this subject in the literature are both limited in number and have been conducted with different medicine combinations in a wide variety of patient populations. The authors thought that further prospective randomised studies are needed to interpret this effect more clearly. Sugammadex, Neostigmine / atropine, Gastrointestinal motility, Laparoscopic cholecystectomy.